2016
DOI: 10.1024/0300-9831/a000293
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Role of Trolox in Hippocampus after Ischemia Reperfusion Injury in Mouse

Abstract: Cerebral ischemia is worldwide the third largest cause of mortality and disability in old people, and oxidative stress plays a considerable role in this process. In this study, for the fi rst time, we evaluated the effects of Trolox as an antioxidative agent in ischemia induced by reperfusion. Twenty-four Syrian male mice were randomly divided into the 3 groups. Both common carotid arteries of Syrian mice were ligated bilaterally for 20 min, blood fl ow was restored and Trolox (50 mg/kg) was immediately inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…[ 18 19 20 ] In cultured bursal cell and neuronal studies, trolox protected against cell death resulting from oxidative stress. [ 21 ] Trolox has an antioxidant role in reducing apoptosis in mouse thymocytes, rabbit myocytes, and anterior pituitary cells. [ 22 23 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 19 20 ] In cultured bursal cell and neuronal studies, trolox protected against cell death resulting from oxidative stress. [ 21 ] Trolox has an antioxidant role in reducing apoptosis in mouse thymocytes, rabbit myocytes, and anterior pituitary cells. [ 22 23 ]…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that trolox can scavenge excess ROS and act as an antioxidant therapy in myocardial injury and diabetic retinopathy (Diaz et al, 2005). Trolox also exhibits a preventive effect on oxidative stress-induced cell death (Sarveazad et al, 2016) and apoptosis in thymocytes, cardiomyocytes, and anterior pituitary cells (Poliandri et al, 2003). This study focused on the anti-aging effect of trolox in MSCs culture.…”
Section: Discussionmentioning
confidence: 99%
“…The Injection speed was 0.25 µlit/min. Mice successfully modeled were randomly assigned (Sarveazad, Babahajian et al 2017) in equal numbers to ve groups (n = 10 per group) as follows:…”
Section: Transplantation Of Dps Cells Into Hippocampusmentioning
confidence: 99%